2012
DOI: 10.1038/ki.2011.369
|View full text |Cite
|
Sign up to set email alerts
|

Dietary salt influences postprandial plasma sodium concentration and systolic blood pressure

Abstract: The plasma sodium concentration has a direct effect on blood pressure in addition to its effects on extracellular volume regulated through changes in the endothelium. The mechanism for elevated blood pressure seen with habitually increased salt intake is unclear, especially the effect of salt in a single meal on plasma sodium concentration and blood pressure. To resolve this we compared the effect of soup with or without 6 g of salt (an amount similar to that in a single meal) on the plasma sodium concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
78
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(86 citation statements)
references
References 23 publications
7
78
1
Order By: Relevance
“…Higher SNa could be a readout for higher sodium intake. This hypothesis would agree with an acute increase in the SNa concentration observed under salt load in normotensive, healthy volunteers [121], however recent evidence suggests higher dietary salt intake may not be associated with higher SNa in HD patients [122]. Figure 3b demonstrates a negative association between predialysis SNa and IDWG, shown also in our analyses from the DOPPS [79,81].…”
Section: Association Between Predialysis Serum Sodium and Volume Oversupporting
confidence: 76%
“…Higher SNa could be a readout for higher sodium intake. This hypothesis would agree with an acute increase in the SNa concentration observed under salt load in normotensive, healthy volunteers [121], however recent evidence suggests higher dietary salt intake may not be associated with higher SNa in HD patients [122]. Figure 3b demonstrates a negative association between predialysis SNa and IDWG, shown also in our analyses from the DOPPS [79,81].…”
Section: Association Between Predialysis Serum Sodium and Volume Oversupporting
confidence: 76%
“…EnNaC endothelial Na + channel concluded that high salt intake compromises the responsiveness of endothelial cells to shear stress [9,10,70]. Studies in humans confirmed what has been learned from animal models: a high-Na + diet (300-350 mmol/day) led to an increase in plasma [Na + ] of 2-4 mmol/l and thus to a loss of NOdependent vasodilation [32,123].…”
Section: Salt Intake Affects Endothelial Functionmentioning
confidence: 51%
“…49 This hypothesis is supported by a number of animal studies; in fact, neonatal uni nephrectomy causes hypertension in adult rats. 17,18 In one human autopsy study in which nephron number was counted, 10 white middle-aged individuals with hypertension had fewer nephrons than did 10 well-matched controls without hypertension. 51 Other autopsy studies that included both Caucasians and African Americans confirmed the association between reduced glomerular number and hypertension in Caucasians but not in African Americans.…”
Section: Nephron Mass and Hypertensionmentioning
confidence: 99%
“…For most individuals, an increase in salt intake induces only a modest and transient rise in arterial pressure. 18 However, the ability of the kidney to adapt to variable intake of sodium differs between indivi duals and is influenced by both genetic and environmental factors. Some individuals are designated as salt sensitive and respond to a high-salt diet with a large rise in blood pressure indicative of a blunted pressure-natriuresis relation ship.…”
Section: Impaired Tubular Handling Of Sodiummentioning
confidence: 99%